Negociação no inquérito policial e sistema jurídico brasileiro - Cogan, Bruno Ricardo Cyrilo Pinheiro Machado (2013)
The scientific work aims to produce knowledge. This is not put into question. Although what is the purpose of that work, or if there is any purpose at all, is a question that must be made ex ante any task. The answer resounds: all knowledge must be turned to the instrument, technology in order to improve people's lives. In legal terms, this should be put in technical terms: improving justice, democracy, human dignity, certainty. However, these basic elements - justice, democracy, human dignity, certainty - have great fluidity, which does not allow them to extract a precise meaning. Same phenomenon occurs in the large themes: people, society, State, Law, State of Law, and Democracy. Witch shall be studied in Unitarian philosophical view of the world. Therefore it is necessary to introduce certain methodological warnings, and it explains the option for analyzing these institutes under the attributes of form and function, starting from abstractions up to very precise and contextualized content of those institutes; in order to propose solutions for fighting crime in a democratic way, especially organized crime. And therefore it is to be studied the possibilities of negotiation within the police investigation in Brazilian Criminal Procedural Law